2020
DOI: 10.1016/j.tipsro.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dose using CBCT and synthetic CT during head and neck radiotherapy: A single centre feasibility study

Abstract: a b s t r a c tObjectives: The study aimed to assess the suitability of deformable image registration (DIR) software to generate synthetic CT (sCT) scans for dose verification during radiotherapy to the head and neck. Planning and synthetic CT dose volume histograms were compared to evaluate dosimetric changes during the treatment course. Methods: Eligible patients had locally advanced (stage III, IVa and IVb) oropharyngeal cancer treated with primary radiotherapy. Weekly CBCT images were acquired post treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…This survey data agrees with the Japanese data in 2018 15 which found single modality DIR (CT‐CT) as the most common DIR image modality pair. Lower DIR usage of CT‐CBCT usage could correspond to additional complexities such as image noise and streaking 32,33 for contour propagation, or image truncation 32,34 for synthetic CT generation 35 which may creep into the implementation of adaptive radiotherapy 24,36,37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey data agrees with the Japanese data in 2018 15 which found single modality DIR (CT‐CT) as the most common DIR image modality pair. Lower DIR usage of CT‐CBCT usage could correspond to additional complexities such as image noise and streaking 32,33 for contour propagation, or image truncation 32,34 for synthetic CT generation 35 which may creep into the implementation of adaptive radiotherapy 24,36,37 …”
Section: Discussionmentioning
confidence: 99%
“…8 In scenarios where DIR is challenging (e.g., tissue appearance or disappearance 6,31 or large deformations 6 ), accurate use requires appropriate management of uncertainties. 4 Data on the use of RIR with multi-modality imaging show the rel- noise and streaking 32,33 for contour propagation, or image truncation 32,34 for synthetic CT generation 35 which may creep into the implementation of adaptive radiotherapy. 24,36,37 Data indicate that more centers have independent DIR software Three different approaches of evaluating IR processes (process satisfaction, staff involvement, key challenges) found that key concerns were registration accuracy classification (satisfactory or not) with appropriate follow-up use.…”
Section: Dir Software Type Dir Software Websitementioning
confidence: 99%
“…The RR and the LCR have published in peer reviewed journals as first author [16] , [17] , [18] . The RR has published as senior author [19] , [20] , [21] . Each RTT has contributed to publications as co-author.…”
Section: Resultsmentioning
confidence: 99%
“…A previous retrospective study used a similar workflow to assess the ability of deforming Halcyon CBCT scans to assess margins for prostate treatments 3 . Other retrospective studies have assessed the feasibility of using deformable registration to a CBCT to replan head‐and‐neck plans and found limitations in the field of view and soft tissue contrast 2,4 . Previously, the limited field of view of CBCT has made the images unusable for treatment planning due to missing patient anatomy, 5 and deforming the target volumes has been discouraged due to the lack of soft tissue contrast and target visibility.…”
Section: Discussionmentioning
confidence: 99%
“…The initial planning CT was registered to the CBCT and then used for replanning, removing the need to repeat patient CT simulation. Previous studies have used a similar approach; due to the limited longitudinal range of CBCT scans, the primary planning CT is required in regions outside of CBCT the field of view 2 . Due to the large field of view of the Halcyon, CBCT large head‐and‐neck tumours can be included in the field of view.…”
Section: Introductionmentioning
confidence: 99%